Influence of Mo2C and TaC additions on the microstructure and mechanical properties of Ti(C, N)-based cermets. Issue 2 (1st February 2016) - Liu, C.; Lin, N.; He, Y.H.
Abstract: In this paper, the effects of Mo2 C and TaC additions on the microstructure and mechanical properties of Ti(C, N)-based cermets prepared through the powder metallurgical method were investigated by scanning electron microscopy, X-ray diffraction and mechanical properties tests. The results show that the microstructure of cermets with core/rim structure have a trend to become finer with increasing Mo2 C and TaC content. The addition of Mo2 C and TaC improve the mechanical properties of Ti(C, N)-based cermets. The cermets with 5 wt% Mo2 C and 5 wt% TaC addition demonstrate excellent hardness and fracture toughness values (HRA: 91.4; K IC : 13.5 MPa m 1/2 ).